A Clinical Profile of Hepatitis A Patients in Jakarta, Indonesia - Adiwinata, Randy; Kristanto, Andi; Richard, Timoteus; Edbert, Daniel; Angelina, Frida; Eppy, Eppy; Mauleti, Ifael Y; Lardo, Soroy; Firmansyah, Iman; Bur, Rika; Ahimsa, Titos; Nelwan, Erni J (UI Scholars Hub, 2017)
Background: To determine the incidence of hepatitis A infections and the clinical profiles of adult patients admitted to public hospitals in Jakarta, Indonesia. Methods: This was a cross-sectional study that utilised consecutive secondary data from internal medicine wards of seven public hospitals in Jakarta between 2011 and 2013. Eligibility criteria included patients over the age of 18 years and an ICD-10 diagnosis code of B15, acute hepatitis A. Case proportion was reported per 1000 people by dividing incidence per year to total in-ward patients. Clinical profiles were reported descriptively. Laboratory results were compared and categorised into groups of patients aged below and above 25 years old. Results: Data revealed that hospitalisations of patients with hepatitis A had decreased from 2011 to 2013. 289 patients were studied, the majority were young adults (18-25 years old) and their common chief complaints were nausea (36%), fever (24%), and jaundice (21%). Higher bilirubin levels were seen in older patients. There were 13 patients coinfected with hepatitis B, one patient coinfected with hepatitis C, and one patient coinfected with HIV. Conclusions: The proportion of hepatitis A infection amongst adults admitted to public hospitals in Jakarta was low and had decreased during the study period. Most of the patients reported classical clinical manifestations. This study found that the targeted age group may benefit from receiving routine hepatitis A vaccinations.